2020
DOI: 10.1159/000509598
|View full text |Cite
|
Sign up to set email alerts
|

Implant Replacement or Removal: What Happens after Capsular Contracture? A German Study Examining Breast Implant Revision Surgery and Patient Choices in 946 Cases

Abstract: <b><i>Introduction:</i></b> Capsular contracture most often leads to implant revision surgery for aesthetic or reconstructive purposes. However, little is known about which operation is chosen when revision surgery has to be performed. We performed analysis of revision indications and performed revision surgery considering implant removal or replacement and additional surgical procedures. To our knowledge, this study presents the largest German single-center analysis regarding implant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In our study, CC accounted for a higher proportion in revision augmentation implant removed cases, the possible reason for this being that the repeated implant removal and placement affects local tissue conditions, leading to a greater susceptibility to CC (40.6% versus 16.5%). The published literature so far shows a higher incidence of CC in revision breast augmentation than in primary breast augmentation, with an incidence of 18.9% in primary augmentation and 28.9% in revision augmentation [ 26 , 30 33 ], which is consistent with our speculation. A comparison of primary breast augmentation versus revision augmentation on CC incidence is not achievable from our data, but it provides strong support for such conclusion.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, CC accounted for a higher proportion in revision augmentation implant removed cases, the possible reason for this being that the repeated implant removal and placement affects local tissue conditions, leading to a greater susceptibility to CC (40.6% versus 16.5%). The published literature so far shows a higher incidence of CC in revision breast augmentation than in primary breast augmentation, with an incidence of 18.9% in primary augmentation and 28.9% in revision augmentation [ 26 , 30 33 ], which is consistent with our speculation. A comparison of primary breast augmentation versus revision augmentation on CC incidence is not achievable from our data, but it provides strong support for such conclusion.…”
Section: Discussionsupporting
confidence: 92%
“…This indicates the importance of a reconstructed breast after implant complications or implant revision surgery, as reflected by numerous studies examining positive body image and quality of life after breast reconstruction. 39–43…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the importance of a reconstructed breast after implant complications or implant revision surgery, as reflected by numerous studies examining positive body image and quality of life after breast reconstruction. [39][40][41][42][43] Swanson 44 stated that a constellation of systemic symptoms known as "breast implant illness" has motivated many women to have their implants removed (this term replaces the old description "human adjuvant disease," which was similarly challenging to define). 1 The role of capsulectomy is unclear in this patient group because there is no known physical cause for this entity.…”
Section: Discussionmentioning
confidence: 99%
“…It seems paradoxical that with IBBR being the most frequent method of breast reconstruction, even more so in the context of the increasing indication of radiation therapy, there is little published evidence on this aspect of breast reconstruction. 19 Based on our own data and other published studies, it can be observed that, even today, there are patients who undergo a mastectomy without being fully informed of the pros and cons of the different reconstructive methods, especially in the cases with radiotherapy. The association between IBBR and radiotherapy has shown failure rates of close to 50%.…”
Section: Discussionmentioning
confidence: 91%
“…It seems paradoxical that with IBBR being the most frequent method of breast reconstruction, even more so in the context of the increasing indication of radiation therapy, there is little published evidence on this aspect of breast reconstruction. 19 …”
Section: Discussionmentioning
confidence: 99%